Integrated Metabolomics and Metagenomics Unveiled Biomarkers of Antioxidant Potential in Fermented Brewer's Grains - Hammad Qamar; Yuanfei Li; Rong He; Muhammad Waqas; Min Song; Dun Deng; Yiyan Cui; Pan Yang; Zhichang Liu; Bilal Qammar; Muhammad Asnan; Xiangxue Xie; et al. (MDPI AG, 2024)
About one-third of the global food supply is wasted. Brewers' spent grain (BSG), being produced in enormous amounts by the brewery industry, possesses an eminence nutritional profile, yet its recycling is often neglected for multiple reasons. We employed integrated metagenomics and metabolomics techniques to assess the effects of enzyme treatments and Lactobacillus fermentation on the antioxidant capacity of BSG. The biotreated BSG revealed improved antioxidant capability, as evidenced by significantly increased (p < 0.05) radical scavenging activity and flavonoid and polyphenol content. Untargeted metabolomics revealed that Lactobacillus fermentation led to the prominent synthesis (p < 0.05) of 15 novel antioxidant peptides, as well as significantly higher (p < 0.05) enrichment of isoflavonoid and phenylpropanoid biosynthesis pathways. The correlation analysis demonstrated that Lactiplantibacillus plantarum exhibited strong correlation (p < 0.05) with aucubin and carbohydrate-active enzymes, namely, glycoside hydrolases 25, glycosyl transferases 5, and carbohydrate esterases 9. The fermented BSG has potential applications in the food industry as a culture medium, a functional food component for human consumption, and a bioactive feed ingredient for animals.